Anatomy and histochemistry of the leaf blade of Syzygium cumini (L.) Skeels - Rafaela Damasceno Sá; Karina Perrelli Randau (Universidade Estadual de Alagoas, 2021)
ABSTRACT: Diabetes is a noncommunicable disease responsible for about 1.6 million deaths in 2016 worldwide. The use of medicinal plants is commonly reported in the literature as an adjuvant in the treatment of diabetes. Syzygium cumini (L.) Skeels, popularly known as azeitona preta or jambolão, is an important medicinal species of the Myrtaceae family used for diabetes. This work aimed to conduct an anatomical and histochemical study of the leaf blade of S. cumini. Semipermanent histological slides were prepared for analysis of the leaf blade in optical microscopy, polarization and scanning electron microscopy. Histochemical tests were performed in cross-sections of fresh leaf slides, using specific reagents for each group of metabolites. Microscopic analysis allowed the identification of important elements in the diagnosis of the species. The histochemical tests evidenced the presence of phenolic compounds, tannins, triterpenes and steroids, alkaloids, essential oils, lipophilic compounds, starch, lignin and calcium oxalate crystals. The results presented contribute to the pharmacobotanical standardization of the species. KEYWORDS: pharmacobotany, microscopy, Myrtaceae.